The Influence of Coronary Heart Disease on Retinal Electrophysiological Examination (Full-field, Pattern and Multifocal Electroretinograms). (3rd April 2022) - Wendelstein, Jascha; Fuchs, Barbara; Reffken, Annika; Bolz, Matthias; Erb, Carl
ABSTRACT: Purpose: To evaluate the influence of coronary heart disease (CHD) on retinal function using a battery of electrophysiological measures. Materials and Methods: We conducted a prospective pilot study comparing 34 patients with a confirmed diagnosis of CHD with 21 healthy participants. Further inclusion criteria were a decimal visual acuity (VA) of 0.8 or better and patient age between 40 and 80 years. All participants were divided into three groups according to the severity of CHD (1, 2 or 3 vessels involved) and one healthy control group. Testing was performed on one eye per patient, either selecting the eye with higher VA or, when equal, selecting randomly. The test procedure consisted of a pattern electroretinogram (ERG), a full-field ERG, a multifocal ERG and an ophthalmic screening examination. Results: Implicit times of the b-wave measured using scotopic full-field ERG were significantly prolonged in all CHD patient groups ( p < .000). Thus, full-field ERG allowed clinicians to differentiate between healthy patients and those suffering from CHD. The multifocal ERG showed significantly different results concerning the amplitude density ( p < .008) in each patient group compared with the control group. CHD had a significant impact on cone-pathway function, although the severity of CHD did not correlate with functional deficiencies of cone cells. Conclusions: Confirmed coronary vascular diseases are correlated with macular cone and bipolar cell function, which can be detected by measuring electrophysiological retinal signals.